Integrating Digital Technologies in Flipped English Teaching for Mixed-Ability Learners - Lola Nazarova (Academia Open, 2026)
General Background: Increasing learner heterogeneity in English language classrooms challenges traditional teacher-centered instruction and calls for pedagogical models that support differentiated learning. Specific Background: The flipped classroom, supported by digital technologies, reallocates instructional time to promote self-paced preparation and active in-class engagement, offering potential benefits for mixed-ability English language teaching. Knowledge Gap: Despite growing interest, empirical evidence remains limited regarding how digitally mediated flipped classrooms systematically address ability-related differences and the underlying pedagogical mechanisms involved. Aims: This study aims to examine the role of digital technologies in supporting flipped English instruction for mixed-ability learners, with a focus on engagement, differentiation, and instructional outcomes. Results: The findings indicate that pre-class digital materials enhance learner readiness and autonomy, while in-class technology-mediated interaction increases participation across proficiency levels and enables more focused teacher feedback. Novelty: The study links flipped classroom practices directly to differentiated instruction theory within authentic classroom contexts. Implications: These results suggest that pedagogically designed, technology-supported flipped instruction can foster inclusive English language learning and inform teacher professional development and future longitudinal research.Keywords : Flipped Classroom, Digital Technology, Mixed-ability Learners, English Language Teaching, Differentiated InstructionHighlight : Pre-class digital materials enhanced learner autonomy and preparedness across proficiency levels. In-class collaborative tools increased participation equity while enabling targeted teacher feedback. Lower-proficiency students benefited from self-paced content; advanced learners excelled in productive tasks.